A relação entre a consciência fonológica e a aquisição da escrita: ressignificando o processo de alfabetização - Caxias, Aldenice da Silva (2015)
This study aimed to analyze if the relationship between phonological awareness and the acquisition of writing is productive for the literacy process. It is a study of qualitative, descriptive and interventionist nature, which was developed with students belonging to the initial cycle of literacy from a public rural school in Curral de Cima (PB). To achieve our purpose, the research was conducted in three stages: the first we apply a pre-test to diagnose levels of phonological awareness and writing of the surveyed students and, by analyzing, observing the difficulties presented written; in the second stage, we developed and applied a proposal of didactic intervention based on the Pacto Nacional Pela Alfabetização na Idade Certa, PNAIC (BRASIL, 2013), with activities that promote the development of phonological awareness and writing; and the third step, we apply a post-test in order to verify the performance of students in relation to the acquisition of writing. Data collected constituted the corpus of this research and the results allowed us to understand how the relationship between phonological awareness and the writing acquisition process is productive to the process of literacy; but for this, it must prioritize the teaching methodology that seeks to provide students an understanding of the alphabetic writing system, through the development of phonological awareness. To give theoretical support to this work were fundamental studies developed by: Smith (2003-2014), Cagliari (2009) and Morais (2012), which based our design on literacy and literacy. Also contributed to the understanding and analysis of the data the reflections of Alves (2009), Capovilla and Capovilla (2010-2011), Lemle (1991), Morais (2012), Kato (1993) and the PNAIC (BRAZIL, 2012-2013) on phonological awareness and written language. From the results of this study, we reflect on our practice of the classroom, correlating the phonological awareness of contributions and written language to reframe the literacy process.